2018
DOI: 10.2307/j.ctvqhsq3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Geological Significance of Larger Benthic Foraminifera

Abstract: on his work in my discussions of the biology of the larger foraminifera as presented in Chapter 1.I would like to refer readers to Prof Lukas Hottinger's outstanding web pages "Illustrated glossary of terms used in foraminiferal research" which can be found at http://paleopolis.rediris.es/cg/CG2006_M02/4_droite.htm. Some of these illustrations are reproduced in this book, courtesy of Prof Hottinger.I would like to thank Prof McMillan for access to his South African collection of larger foraminifera, Dr Michell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
259
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(265 citation statements)
references
References 215 publications
(427 reference statements)
5
259
0
1
Order By: Relevance
“…A notable feature of Cipit boulders, according to Fürsich & Wendt (1977) and to Biddle (1984), is the significant absence of dolomitization and diagenesis in most of them, which allows the identification of the biota and the microfacies. This feature was also recognized by Reitner (1987), Russo et al (1991), Neuweiler & Reitner (1995), Russo (2005) and Sánchez-Beristain & Reitner (2012, 2018. In turn, the microfacies and biotic heterogeneity at the Cipit boulders from the St Cassian Formation have since long been defined (e.g.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…A notable feature of Cipit boulders, according to Fürsich & Wendt (1977) and to Biddle (1984), is the significant absence of dolomitization and diagenesis in most of them, which allows the identification of the biota and the microfacies. This feature was also recognized by Reitner (1987), Russo et al (1991), Neuweiler & Reitner (1995), Russo (2005) and Sánchez-Beristain & Reitner (2012, 2018. In turn, the microfacies and biotic heterogeneity at the Cipit boulders from the St Cassian Formation have since long been defined (e.g.…”
mentioning
confidence: 70%
“…For instance, Popa et al (2014) reported Tubiphytes and cement crusts as the main reef builders from the Anisian of North Dobrogea, Romania. The role of microencrusters during the Triassic continued to take more relevance in the Ladinian-Carnian [Flügel et al 2002 (and references therein); Flügel 2010;Sánchez-Beristain & Reitner 2012, 2018Sanchez-Beristain et al 2013;Gale et al 2016Gale et al , 2018], until the Carnian extinction event (Benton et al 2018) and up to the Norian-Rhaetian in the Tehyan realm [e.g. Schäfer 1979;Senowbari-Daryan 1980;Bernecker et al 1999;Flügel et al 2002 (and references therein); Cherchi & Schroeder 2010;Senowbari-Daryan et al 2011;Uţa 2012;Senowbari-Daryan & Link 2018].…”
Section: Although Koskinobullina Socialis (Figs 7 8) Canmentioning
confidence: 99%
See 3 more Smart Citations